1982
DOI: 10.1080/00914038208077979
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rheological Properties of Compounds on Fiber Formation in Mixtures of Incompatible Polymers

Abstract: Mixturesoflinearpolyethylene with polystyrene were used in studying the fiber formation pattern of mixtures of incompatible polymers whose melts were forced through dies. Variables included the viscosity of the components, mixture preparation conditions, and shear stress. It has been established that the process of fiber formation occurs within a definite range of shear stresses, dependent on the viscosity ratio of the fiber-forming polymer and the polymer serving as the dispersion medium. When this ratio is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 14 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…The formation of micro‐ and nanofibrillar phase morphology of polymer blends was one of the most challenging tasks in polymer research during the last decades. Numerous studies on morphology development of polymer blends in twin‐screw extruders as well as in spinneret channels, and the effects of various processing parameters on it have been published . By contrast, few studies have tried to investigate the morphological variations of polymeric blend systems after extrusion from the spinneret orifices into fibers .…”
Section: Introductionmentioning
confidence: 99%
“…The formation of micro‐ and nanofibrillar phase morphology of polymer blends was one of the most challenging tasks in polymer research during the last decades. Numerous studies on morphology development of polymer blends in twin‐screw extruders as well as in spinneret channels, and the effects of various processing parameters on it have been published . By contrast, few studies have tried to investigate the morphological variations of polymeric blend systems after extrusion from the spinneret orifices into fibers .…”
Section: Introductionmentioning
confidence: 99%
“…The changes in the rheological properties of multicomponent polymers are usually caused by the characteristics of the components themselves and the interaction between the components, which can be observed via the motion state of the polymer chain under amplitude oscillation shear (SAOS) using a rotational rheometer. [23][24][25] To investigate the effect of IL on the rheological properties of PEEK, the dynamic rheological behaviors including dynamic storage modulus (G 0 ), loss modulus (G 00 ), and complex viscosity, were studied with respect to the angular frequency of neat PEEK and PEEK/IL blends under SAOS, as shown in Figure 3. From Figure 3A,B, it can be observed that the G' and G" of all PEEK/IL blends increase with an increase in the angular frequency from 0.1 to 100 rad/s, which is due to the shortened relaxation time of the molecular chain at high frequency.…”
Section: Rheological Properties Of Peek/il Blendsmentioning
confidence: 99%